1990
DOI: 10.1111/j.1600-0447.1990.tb05462.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term course of depression following attempted suicide: a preliminary report

Abstract: The course of depression over 1 week in patients admitted to hospital following an attempted suicide was examined utilizing a clinical interview, the Zung Self-Rating Depression Scale, the Levine-Pilowsky Depression (LPD) Questionnaire and the Hamilton Rating Scale for Depression. On all measures the group had depression of moderate to marked severity at the time of attempted suicide. In males there was a statistically and clinically significant reduction in severity of depression over 1 week. This trend was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The potential for an SDT-or MIbased approach to increase depressed clients' engagement in treatment that may reduce suicide-related behavior or depression is an important line of research to pursue. We call for such research because individuals who are depressed and attempt suicide may experience a sudden improvement in their depressive symptoms (Bronisch, 1992;Davis, 1990;Jallade, Sarfati, & HardyBayle, 2005;Van Praag & Plutchik, 1985;Walker, Joiner, & Rudd, 2001). Such improvement, which may be dramatic and temporary (Watzlawick, Weakland, & Fisch, 1974), may create a window of opportunity that is particularly well suited to interventions that target clients' motivation and energy.…”
Section: Future Directionsmentioning
confidence: 96%
“…The potential for an SDT-or MIbased approach to increase depressed clients' engagement in treatment that may reduce suicide-related behavior or depression is an important line of research to pursue. We call for such research because individuals who are depressed and attempt suicide may experience a sudden improvement in their depressive symptoms (Bronisch, 1992;Davis, 1990;Jallade, Sarfati, & HardyBayle, 2005;Van Praag & Plutchik, 1985;Walker, Joiner, & Rudd, 2001). Such improvement, which may be dramatic and temporary (Watzlawick, Weakland, & Fisch, 1974), may create a window of opportunity that is particularly well suited to interventions that target clients' motivation and energy.…”
Section: Future Directionsmentioning
confidence: 96%
“… We investigated suicide “catharsis” as evidenced by decreased suicidality following a suicide attempt. Past research has examined this issue with mixed results (Bronisch, 1992; Davis, 1990; van Praag & Plutchik, 1985). In the present study, we examined Modified Scale for Suicide Ideation (MSSI) scores for 198 suicidal men during suicidal crisis, prior to entry into a treatment study, and again at 1‐month and 12‐month follow‐ups.…”
mentioning
confidence: 99%
“…This notion of catharsis has been espoused by several researchers (Bronisch, 1992; Davis, 1990; van Praag & Plutchik, 1985) who investigated changes in symptoms following a suicide attempt. These researchers and others have used the terms catharsis and cathartic effect to describe the significant decrease in symptoms following a suicidal crisis (see Bronisch, 1992; Davis, 1990; Newson‐Smith, 1979; van Praag & Plutchik, 1985). All agree that the concept of suicide catharsis warrants further empirical study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beck (1996) suggested that previous SB sensitizes suicidal thoughts and behaviors, such that they become more autonomous and easily precipitated. Self-aggression ameliorates the physical and emotional tension that precedes SB, depressive and anxiety symptoms, and painful emotions (i.e., hopelessness, emptiness) (Davis, 1990;Jallade, Sarfati, and Hardy-Bayle, 2005;Sarfati, Bouchaud, and Hardy-Bayle, 2003;van Praag and Plutchik, 1985;Walker et al, 2001). In a pilot fMRI study with eight female subjects, mental pain triggering SB was associated with decreased prefrontal activity, whereas "planning and acting out suicidal impulses in response to mental pain" was related to increased activity in the frontal cortex, suggesting that SB reduces mental pain (Reisch et al, 2010).…”
Section: Putative Mechanisms Involved In the Development Of Addictionmentioning
confidence: 99%